Employee Perception, Accounting Knowledge, JKP Contribution Management, BPJS Employment, Public Agency - Ratnasari; Hurian Kamela (Research of Accounting and Governance, 2026)
The Job Loss Guarantee (JKP) Program of the Social Security Administering Agency for Employment (BPJS Ketenagakerjaan) aims to provide social security to workers who lose their jobs. The purpose of this study was to examine the effect of accounting knowledge and workers' attitudes on JKP contribution management. The quantitative research methodology included a survey with 102 participants and the use of multiple linear regression and descriptive statistics. The results showed that Accounting Knowledge and Worker Perception had a significant and positive effect on JKP Contribution Management. Compared to accounting knowledge, worker perception had a greater influence. This enhances the effectiveness of the JKP program management and provides recommendations for the Social Security Agency for Workers (BPJS Ketenagakerjaan) in optimising social protection services for workers.